COMMAND AND CONTROL OF A BIOMIMETIC STRUCTURE USING THE TCS-230 COLOR SENSOR AND APDS-9960 GESTURE SENSOR - Marian IONESCU; Ilie BORCOSI (Fiabilitate şi Durabilitate, 2024)
This paper presents a way to use the TCS-230 color sensor in combination with the APDS-9960 gesture sensor. In order to validate the operation and usefulness of these sensors, it was proposed to carry out an experiment aimed at the command and control of the Chimpanzee Alive animatronic structure. Thus, during the experiment, the animatronic platform presents the following operating protocol: upon the appearance of a red, green or blue light/object, the animatronic structure will perform certain eye and head movements; upon the disappearance of these stimuli, the animatronic structure will stop executing these movements, returning to its initial position. This cessation of the movements of the animatronic structure is achieved by means of the gesture sensor which is able to detect certain simple gestures of the user, without direct contact with it. By moving the hand in front of the sensor in a certain arbitrarily chosen direction, the eye or head movements of the animatronic structure are stopped.